Contemplative Pedagogy and Revitalization of Teacher Education - Bai, Heesoon; Scott, Charles; Donald, Beatrice (Alberta Journal of Educational Research, 2010)
The prevailing conception and practice of education perpetuates a civilization saturated with a deep sense of ontological disconnect and axiological crisis in all dimensions of human life. We examine the disconnect from body, senses, and world in the practice of education. We explore the possibilities in the burgeoning contemplative education movement for reconnection offered by holistic, experiential approaches to learning, in particular, contemplative practices that manifest the arts of somatic, sensuous, relational, and contextual awareness.